2002
DOI: 10.1590/s0085-56262002000100001
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the leg exocrine glands in termites(Isoptera)

Abstract: ABSTRACT.A survey of the leg exocrine glands in the termite workers of 16 species of the families Kalotermitidae and Termitidae was carried out through scanning electron microscope. Glandular openings were not found in the legs of Anoplotermes sp., Ruptitermes sp. (Apicotermitinae, Termitidae) or Glyptotermes planus (Kalotermitidae), but they are present, spread over the ventral surface of the first, second and third tarsomeres of other Termitidae such as Armitermes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
(5 reference statements)
0
6
1
Order By: Relevance
“…Bacchus (1979) described clusters of class-3 gland cells that open into sunken pore plates on the distal portion of the tibia of the 6 legs in several Rhinotermitidae termites. The function of these glands is unclear (Bacchus, 1979), although their peculiar opening through distinct pore plates (Costa- Leonardo, 1994;Soares and Costa-Leonardo, 2002) is very different from the dorsodistal tibial glands here reported for wasps and ants.…”
Section: Dorsodistal Tibial Glandcontrasting
confidence: 59%
See 1 more Smart Citation
“…Bacchus (1979) described clusters of class-3 gland cells that open into sunken pore plates on the distal portion of the tibia of the 6 legs in several Rhinotermitidae termites. The function of these glands is unclear (Bacchus, 1979), although their peculiar opening through distinct pore plates (Costa- Leonardo, 1994;Soares and Costa-Leonardo, 2002) is very different from the dorsodistal tibial glands here reported for wasps and ants.…”
Section: Dorsodistal Tibial Glandcontrasting
confidence: 59%
“…Later, Soares and Costa-Leonardo (2002) and Costa- Leonardo et al (2015) found a more widespread occurrence of ventral pores on tarsomeres t1-t2-t3 in several termite groups. According to Bacchus (1979), these glands may have a role in defence, whereas Costa- Leonardo et al (2015) suggest a role in antenna cleaning or production of antibiotics.…”
Section: Ventral Tarsomere Glandsmentioning
confidence: 94%
“…Tibial gland is a term introduced by Gonçalves et al (2010) to refer to the tibial part of the tarsal gland. Tarsal glands presence is highly variable among taxa, but they may occur on the distal side of the tibia, and on the 1st, 2nd and 3rd tarsomere (Bacchus, 1979;Soares and Costa-Leonardo, 2002), and the ultrastructure of the secretory cells is identical between tibia and tarsal segments at least in Reticulitermes lucifugus ( Sobotník and Weyda, 2002). In conclusion, our opinion is that termite glandular set comprises 19 distinct known exocrine organs, that are epidermal tegumental glands, bicellular unit tegumental glands, frontal gland, labral gland, mandibular base glands, mandibular glands, labial glands, tarsal glands, lateral thoracic glands, dehiscent glands, tergal glands, sternal glands, posterior sternal glands, spermathecal gland, pleural abdominal glands (reviewed by Gonçalves et al, 2010), hypopharyngeal gland (Brossut, 1973), crystal glands ( Sobotník et al, , 2014, posterior tergal glands (CostaLeonardo and Haifig, 2010) and the clypeal gland described here.…”
Section: Discussionmentioning
confidence: 99%
“…1998; Cruz‐Landim 2002), but otherwise we do not know of the description of coxal glands in social Hymenoptera. A survey of the leg exocrine glands in termites also does not mention coxal glands in this group (Soares and Costa‐Leonardo 2002), although there is a brief report of ‘epidermal glands’ in the coxae of neotenic reproductives of Prorhinotermes simplex termites (Šobotník et al . 2003).…”
Section: Discussionmentioning
confidence: 99%